Tuberculosis at An Unusual Site (Journal of Medicine, 2010)
Tuberculosis involving the anorectal region is a rare extrapulmonary form of the disease. We report two cases of isolated rectal tuberculosis with different presentations. On both instances, diagnosis was confirmed by histological examination and treated with anti-tuberculous drugs with successful outcome. Keywords: Tuberculosis, abdominal tuberculosis, extrapulmonary, gastrointestinal, rectal. DOI:10.3329/jom.v11i1.4277 J Medicine 2010: 11: 67-69